2023
DOI: 10.1248/bpb.b22-00772
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation Pathway of VEGF Gene Expression Is Different between 2D Cells and 3D Spheroids in Human Lung Cancer Cells

Abstract: Angiogenesis is involved in the malignant transformation of cancers. Vascular endothelial growth factor (VEGF) is important in inducing angiogenesis. Cultured cells play an important role in analyzing the regulation of VEGF expression, and it is revealed that VEGF expression is induced under hypoxia. However, it has been shown that there are differences in the pathway for gene expression between two-dimensional (2D) cells and in vivo cells. Three-dimensional (3D) spheroids constructed in 3D culture with a gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…In essence, the increase in HIF-1α appears to be associated with the decrease in VEGFA expression. This conclusion aligns with the results reported by Ryo Onodera (Onodera et al, 2023).…”
Section: The Effect Of Cb-nps On Tumor Angiogenesissupporting
confidence: 93%
“…In essence, the increase in HIF-1α appears to be associated with the decrease in VEGFA expression. This conclusion aligns with the results reported by Ryo Onodera (Onodera et al, 2023).…”
Section: The Effect Of Cb-nps On Tumor Angiogenesissupporting
confidence: 93%
“… 23 Additionally, it has been reported that the VEGF gene expression pathways differ between 2D cell cultures and 3D spheroids, and in certain scenarios, increased HIF1α levels are associated with reduced VEGFA expression. 24 These factors could potentially explain the lack of significant results in the tube formation assay following SCG2 overexpression (Figure 6E ). Considering the intricate nature of disease processes and the involvement of various factors, if there is indeed an association between elevated HIF1α and decreased VEGFA, it is probable that additional regulatory mechanisms and modulators contribute to this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…[10,11] Studies have shown that the hypoxic environment of the cells in the middle of the spheroids can not only enhance their adaptation to ischemic tissue, [12] but also promote the secretion of more cytokines, such as VEGF, bFGF, and FGF2. [13] In a nude mouse model, scholars have also found that ADSCs spheroids have a higher retention rate than monolayer cells and have a better potential for treatment by intramuscular injection of ADSCs. [14] In our study, we tested whether 3D spheroid culture could regulate autophagy, apoptosis, senescence, and secretion of cytokines and further analyzed the influence of spheroid formation on neovascularization and the survival of transplanted fat particles.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10,11 ] Studies have shown that the hypoxic environment of the cells in the middle of the spheroids can not only enhance their adaptation to ischemic tissue, [ 12 ] but also promote the secretion of more cytokines, such as VEGF, bFGF, and FGF2. [ 13 ] In a nude mouse model, scholars have also found that ADSCs spheroids have a higher retention rate than monolayer cells and have a better potential for treatment by intramuscular injection of ADSCs. [ 14 ]…”
Section: Introductionmentioning
confidence: 99%